Catalytic agent for strategic innovation ambidexterity: The role of human capital / Faizah Mashahadi … [et al.] - Mashahadi, Faizah; Ahmad, Noor Hazlina; Mohamad, Osman; Mohayidin, Mohd Ghazali; Mahmud, Razmah; Abd Razak, Noraznira; Marmaya, Najihah Hanisah (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
Developing exploitation and exploration innovation capability is enormously critical for small and medium enterprises (SMEs) to attain comprehensive endurance in borderless business battlefield. To better understand the extent to which SMEs realize strategic innovation ambidexterity, this study develops a theoretical framework that associates human capital to strategic innovation ambidexterity. Grounded by the Theory of Dynamic Capability, this present study examines the effects of the subsequent predecessor in predicting technological and non-technological innovation ambidexterity among SMEs operating internationally specifically; general human capital and specific human capital. Data were collected via self-administered questionnaires from herbal-based SMEs who participated in this study. A quantitative approach was adopted, and hypotheses were tested using Partial Least Squares (PLS) analysis. Findings showed that general and specific human capital positively influenced the development of strategic technological and non-technological ambidexterity. This study provides evidence on the pivotal role of human capital in SMEs located in a developing country.